Effect of acute caffeine intake on hit accuracy and reaction time in professional e-sports players - Sainz, I.; Collado-Mateo, D.; Del Coso, J. (Physiology & Behavior, 2020)
Caffeine is considered a cognitive enhancer at low to moderate doses because it improves alertness, vigilance, attention, and reaction time. However, no previous investigation has assessed the effect of acute caffeine intake on e-sports-specific performance. The aim of this investigation was to determine the effect of the ingestion of 3 mg per kg of body mass on simple reaction time in a color test and on hit accuracy and reaction time during a first-person shooting game. Fifteen professional e-gamers (age= 22 ± 3 years) participated in a double-blind, cross-over, randomized experimental trial. In two trials 3 days apart, participants either ingested a placebo (cellulose) or 3 mg/kg of caffeine in an opaque and unidentifiable capsule. After a 45-min wait for substance absorption, participants performed 5 attempts at a simple reaction time test and completed a first-person shooting game that included 3 attempts at a 2-min game with 60 fixed targets (180 targets in total). Reaction times (in both tests) and accuracy in hitting the targets (only in the shooting game) were measured. In comparison to the placebo, caffeine decreased simple reaction time (0.20 ± 0.01 vs. 0.19 ± 0.01 s, P < 0.01), the mean time taken to hit the targets (0.92 ± 0.07 vs. 0.88 ± 0.07 s, P < 0.01) and enhanced hit accuracy (98.8 ± 0.92 vs. 99.8 ± 0.35% of targets hit, P < 0.01). In summary, the acute ingestion of 3 mg/kg of caffeine reduced the time taken to react to a simple stimulus, decreased the time taken to hit a fixed target and improved accuracy in hitting the target in a first-person shooting game in professional e-gamers. Thus, the caffeine ingestion (3 mg/kg) might be considered as an ergogenic aid for e-sports gamers based on its effect to enhance hit accuracy and time.